Chairman's report: elephant and rhino surveys and some action - David Western (Pachyderm)
Reviews ongoing poaching and ivory exports noting the decline from about 100 tons in 1976 to 681 tons in 1979 has held steady since then, however the tusk size has gone down which means that younger animals are taken. Notes different export rules for carved ivory and raw ivory and suggests that this situation should be assessed. Notes the continuing problem of high export figures from Sudan and suggests that CITES rules could be more effectively utilized in this and other exporting and importing situations and could legislation on minimum tusk size.